An Observational Study of the Pharmacokinetics of Surgeon-Performed Intercostal Nerve Blockade With Liposomal Bupivacaine for Posterior-Lateral Thoracotomy Analgesia. (December 2020) - Manson, William C.; Blank, Randal S.; Martin, Linda W.; Alpert, Salome B.; Dobrzanski, Tomasz P.; Schneider, Eric B.; Ratcliffe, Sarah J.; Durieux, Marcel E.
Abstract : BACKGROUND: Intercostal nerve blocks with liposomal bupivacaine are commonly used for thoracic surgery pain management. However, dose scheduling is difficult because the pharmacokinetics of a single-dose intercostal injection of liposomal bupivacaine has never been investigated. The primary aim of this study was to assess the median time to peak plasma concentration ( T max ) following a surgeon-administered, single-dose infiltration of 266 mg of liposomal bupivacaine as a posterior multilevel intercostal nerve block in patients undergoing posterolateral thoracotomy. METHODS: We chose a sample size of 15 adults for this prospective observational study. Intercostal injection of liposomal bupivacaine was considered time 0. Serum samples were taken at the following times: 5, 15, and 30 minutes, and 1, 2, 4, 8, 12, 24, 48, 72, and 96 hours. The presence of sensory blockade, rescue pain medication, and pain level were recorded after the patient was able to answer questions. RESULTS: Forty patients were screened, and 15 patients were enrolled in the study. Median (interquartile range [IQR]) T max was 24 (12) hours (confidence interval [CI], 19.5–28.5 hours) with a range of 15 minutes to 48 hours. The median (IQR) peak plasma concentration ( C max ) was 0.6 (0.3) μg/mL (CI, 00.45–0.74 μg/mL) in a range of 0.3–1.2. The serum bupivacaine concentration was undetectable (<0.2 μg/mL) at 96 hours in all patients. There was significant variability in reported pain scores and rescue opioid medication across the 15 patients. More than 50% of patients had return of normal chest wall sensation at 48 hours. All patients had resolution of nerve blockade at 96 hours. No patients developed local anesthetic toxicity. CONCLUSIONS: This study of the pharmacokinetics of liposomal bupivacaine following multilevel intercostal nerve blockade demonstrates significant variability and delay in systemic absorption of the drug. Peak serum concentration occurred at 48 hours or sooner in all patients. The serum bupivacaine concentration always remained well below the described toxicity threshold (2 μg/mL) during the 96-hour study period.